Preparation of nickel cobalt oxide on titania nanotubes via wet impregnation for supercapacitor - Chua, Chi Wing (2018)
Titania nanotubes array and nickel cobaltite are both widely studied metal oxide materials for applications in the field of energy storage and delivery. However, the electrochemical capacitive charge storage of titania nanotubes is generally poor because of their inferior electrical conductivity. A number of attempts at chemical modifications by doping and making composites have been performed but the effect of decorating the surface of titania nanotubes with ternary metal oxide has not been adequately addressed. This study aims to evaluate the electrochemical performance of combining titania nanotubes array with nickel cobaltite for the purpose of fabricating composite electrochemical capacitors. Further, this study also aims to evaluate the possibility of using wet impregnation method to introduce metal oxides onto titania nanotubes array. The techniques that were used in the characterisation of the samples were X-ray diffraction (XRD), cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), electrochemical impedance spectroscopy (EIS), field-emission–scanning electron microscopy (FESEM), and energy dispersive X-ray microanalyses (EDX). Parameters that were studied included anodisation duration, anodisation potential, initial molar concentration of nickel(II) nitrate solution and cobalt(II) nitrate solution, thermal treatment temperature of the precursor solution, impregnation duration, and types of electrolytes. The optimum synthesis conditions for the unmodified titania nanotubes were 60 minutes anodisation duration and 17 V anodisation potential, whereas the optimum synthesis conditions for the nickel cobaltite – titania nanotubes composite were 1.0 M initial molar concentration of nickel (II) nitrate solution and cobalt(II) nitrate solution, thermal treatment temperature of the precursor solution was 375 °C, and an impregnation duration of 60 minutes. The nickel cobaltite – titania nanotubes composite performed optimally in 1.0 M KOH. ii By the use of optimised synthesis conditions, it was found that the composite possessed the best electrochemical behaviour in 1.0 M KOH. CV tests demonstrated that the composite exhibited a small degree of electrocatalytic behaviour due to a sharp increase in current density in the 0.6 V region. The areal capacitance was 214.76 μF/cm2 at 350 μA/cm2, which decreased to 210.02 μF/cm2 when the current density increased to 400 μA/cm2. Further, it was found that the composites relied largely of electric double layer charge storage mechanism. Cycle stability study shows the composite deteriorated to 62.38% in 250 cycles of charge-discharge. Micrographs of the composite has shown that the nickel cobaltite nanoclusters preferred to deposit on the surface of the nanotubes rather than on the inside of the nanotube pores. EDX microanalyses indicated that the deposition of nickel and cobalt was very small, which were ~0.06 mol.% and ~0.13 mol.%, respectively.